2014
DOI: 10.1134/s207005041403012x
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of n-heptane on Pt/MOR/Al2O3 catalysts

Abstract: Pt/MOR/Al 2 O 3 catalysts with mordenite zeolite contents of 10 to 50 wt % are prepared. Solutions of H 2 PtCl 6 and [Pt(NH 3 ) 4 ]Cl 2 are used as precursors of Pt. It is shown by means of transmission electron microscopy (TEM) that the localization of platinum on a MOR/Al 2 O 3 mixed support depends directly on the nature of the metal's precursor. The catalysts are tested in the isomerization of n heptane. It is shown that the best samples of catalysts provide yields of the target products (dimethyl and trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Incorporation of Al 2 O 3 support into the zeolite structure can also influences the activity of a 0.3 wt.%Pt/H-MOR catalyst [129]. It could be observed that, for a 10 to 50 wt.% alumina additions, the higher the alumina loading the higher the n-heptane conversion.…”
Section: Please Insertmentioning
confidence: 94%
“…Incorporation of Al 2 O 3 support into the zeolite structure can also influences the activity of a 0.3 wt.%Pt/H-MOR catalyst [129]. It could be observed that, for a 10 to 50 wt.% alumina additions, the higher the alumina loading the higher the n-heptane conversion.…”
Section: Please Insertmentioning
confidence: 94%
“…Therefore, several metal species including Pd, Ga, Ni, Ir, Zn, Fe, Mo, Co, Cu, Ru, Zr, and Pt were loaded on the zeolite framework for better stability, selectivity, and activity by different methods including the impregnated and supercritical CO 2 . ,, Among them, platinum (Pt) is known as an extremely effective metal for dehydrogenation and hydrogenation reactions. Pt loading over the zeolites increased the bifunctionality of catalysts by modifying the acidic active sites and formation of redox sites that are considered as highly effective and stable for n -C 5 –C 6 –C 7 alkanes hydroisomerization. Yeh et al demonstrated that loading of Pt over ZSM-5 (Pt/ZSM-5) by the impregnated method showed 9.8% and 9.2% n -hexane conversion at 633 and 723 K respectively with 137 bar constant pressure. They also revealed that Pt/ZSM-5 resulted in the maximum yield of about 12.5 and 8.9% for iso -C 6 isomers with an average 9.2% production of the cracked product at the same temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Все это обусловливает необходимость разработки высокоэффективных катализаторов без благородных металлов, позволяющих осуществлять процесс риформинга в принципиально новых условиях без присутствия газообразного водорода. В настоящее время в промышленности для изомеризации пентан-гексановых фракций применяются хлорированный Pt/Al 2 O 3 и Ptцеолитный катализатор на основе морденита [9]…”
Section: Introductionunclassified